Improved early recovery after TKA through an app-based, feedback-controlled active muscle training - A prospective randomized trial. Issue 4 (27th April 2017) - Weber-Spickschen, Sanjay; Hardt, Sebastian; Horstmann, Hauke; Krettek, Christian
Aims and Objectives: : The aim of this prospective randomized controlled trial was to evaluate if an app-based, feedback-controlled active muscle training can be used to improve the early outcome after total knee arthroplasty. Materials and Methods: : Sixty patients (mean age 67.3 years, range 45 to 84) awaiting primary total knee arthroplasty (TKA) were randomized into a control- and training group. Both Groups followed an identical postoperative protocol. Additionally, the training group performed an appbased, feedback-controlled active muscle training multiple times daily postoperatively. Outcome measures were active and passive range of motion, pain at rest and in motion, knee extension strength, the Timed "Up and Go", 10 Meter Walk Test, 30 Second Chair Stand Test, Knee Injury and Osteoarthritis Outcome Score (KOOS), Knee Society Score (KSS) and inpatient data. Results: : Mean time to follow-up was 6.88 days in the control group and 6.59 days in the training group for a total of 47 patients (78.3 percent follow-up). The training group used the GenuSport Knietrainer a total of 18.4 times (range 6 to 42 times) on average. Active range of motion was 11.4 degrees higher in the training group (p=0.038), while passive range of motion was almost the same (p=0.906). Mean pain was significantly lower in the training group both at rest (p=0.01) and in motion (p=0.002). The training group reported significantly better outcomes in the KOOS Activities of Daily Living Score (p=0.037). No significant differences were observed in KOOS pain, symptoms, sports and quality of life (p=219, p=0.625, p=0.204, p=0.452, respectively). The KSS Knee Score and KSS Function Score were significantly better in the training group (p<0.001, p=0.011, respectively). Conclusion: : An app-based and feedback-controlled active muscle training can significantly improve the early outcome after total knee arthroplasty, particularly reduce pain and improve the range of motion. More training had better effects on the outcome than less training. Treatment costs could possibly be reduced. These findings are highly relevant regarding rising expectations from patients and the need to reduce costs in the health care system. Further studies with a longer follow up are necessary.